A questão do sujeito em Foucault: entre a sujeição de si e o governo de si - Rosilene Maria Alves Pereira (2012)
This thesis analyses the question of the Subject and its modes of subjection and subjectivisation in Foucaults studies from 1975 to 1984. It is focused on the Genealogical phase of his research,specifically in his final courses and works in which the Political and Ethica concerns are predominating. The Foucaults Geneaogical researches always lead to contrast the Greek and Modern experiences. From our point of view, by taking that contrast from the perspective of the Subjet question,we aim to restore the connection between subjectivity and history. At the end we show how Foucaults genealogy will change the nature of Philosophical praxis itself by reinforcing the nexus between Philosophy and History, and doing so we claim his Philosophical project is the is the making of a critical history of reason by following the tracks of Kantian Criticism. So we may say that there is the Foucautian way of thinking, with his attention to history and disposition to analyze objects that Philosophical tradition had put on side like sexuality, reclusion, and madness _, a conception of Philosophy that opens an interesting and germinal path to Contemporary philosophy.